Implementasi Network Automation untuk Backup Konfigurasi Perangkat Jaringan - Melanie Putria; Agustinus Marcello Soebiantoro; Harry Aprianto; Wasis Haryono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
PT Multipolar Technology Tbk is a leading information technology (IT) solutions provider in Indonesia, specializing in system integration, IT consulting, and outsourcing services. As part of the Lippo Group business ecosystem, the company plays a pivotal role in driving digital transformation across various industries, including banking, retail, telecommunications, and government sectors. Through strategic partnerships with global technology leaders such as IBM, Oracle, Cisco, and Microsoft, Multipolar Technology delivers comprehensive solutions encompassing hardware, software, cloud services, and data center infrastructure. Additionally, through its subsidiary PT Visionet Data Internasional (VisioNet), the company offers large-scale managed services. Its commitment to service excellence and technological advancement positions Multipolar Technology as a trusted partner in the digital journey of organizations throughout Indonesia.